2000
DOI: 10.1017/s135583820099215x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual structure formed by antisense-target RNA binding involves an extended kissing complex with a four-way junction and a side-by-side helical alignment

Abstract: The antisense RNA CopA binds to the leader region of the repA mRNA (target: CopT). Previous studies on CopA-CopT pairing in vitro showed that the dominant product of antisense RNA-mRNA binding is not a full RNA duplex. We have studied here the structure of CopA-CopT complex, combining chemical and enzymatic probing and computer graphic modeling. CopI, a truncated derivative of CopA unable to bind CopT stably, was also analyzed. We show here that after initial loop-loop interaction (kissing), helix propagation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 46 publications
5
50
0
Order By: Relevance
“…This progression is dependent on the presence of bulges in the hairpin stems 60 that presumably aid the transformation by destabilizing the stems. Intriguingly, the number of base pairs in the two intermolecular helices is thought to be 15 with six bases in each of the loops connecting the ends of these helices, 58,59 which is extremely similar to the detailed structure of our kissing complexes.…”
Section: A Topologically Unlinked Complex; Lk =mentioning
confidence: 68%
See 1 more Smart Citation
“…This progression is dependent on the presence of bulges in the hairpin stems 60 that presumably aid the transformation by destabilizing the stems. Intriguingly, the number of base pairs in the two intermolecular helices is thought to be 15 with six bases in each of the loops connecting the ends of these helices, 58,59 which is extremely similar to the detailed structure of our kissing complexes.…”
Section: A Topologically Unlinked Complex; Lk =mentioning
confidence: 68%
“…Furthermore, a structure very similar to that reported here has also been identified for an "extended" kissing complex between messenger and antisense RNA that also involves parallel helices and a four-way junction. [58][59][60] As with any study with a coarse-grained model, one needs to consider how robust the results are and whether they might reflect any weaknesses of the model. We explicitly checked this for the repulsion between backbone sites in Section III D and found that although the results could change significantly when varying this parameter, our current value appears to be physically most reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the dimer initiation complex of the HIV-genomic RNA, a metastable intermolecular kissing interaction culminates in a linear duplex isoform stabilized by intermolecular base pairing (20,44). A kissing interaction also initiates the binding of the antisense RNA CopA to its target, CopT, but the outcome of this interaction is an unusual four-way junction defined by the predicted base stacking arrangements of intramolecular helices and newly formed intermolecular helices (19,45). In these types of kissing complexes, the intramolecular helices contributing to the initial kissing complex are replaced with intermolecular helices within an extended complex.…”
Section: Discussionmentioning
confidence: 99%
“…Kissing complexes in which the loop nucleotides are complementary can form stable dimers that contain intermolecular base pairs between the loop nucleotides only. Other stem-loops with more extensive complementarity sometimes form unstable kissing complexes, which are quickly remodeled into stable duplex or cruciform isoforms (18)(19)(20). Secondary structure remodeling involves breaking intramolecular base pairs in each hairpin and using the bases to form intermolecular helices.…”
mentioning
confidence: 99%
“…For example, two copies of a genomic sequence have been proposed to play a critical role in the initiation of HIV-1 viral replication. Many RNA-RNA dimers are stabilized by tertiary interactions such as kissing-loop interactions and pseudoknotted interactions between the RNAs (Paillart et al 1996(Paillart et al , 2004Jossinet et al 1999;Kolb et al 2000aKolb et al ,b, 2001aRussell et al 2004). The RNA-RNA interactions mentioned in the above biological processes demonstrate 1 the need to have a model that can treat (1) conformational changes, (2) complex interplay between intermolecular and intramolecular base pairing, and (3) kissing interactions in RNA-RNA complexes.…”
Section: Introductionmentioning
confidence: 99%